INCLUSIVE EDUCATION IN BANGKA BELITUNG PROVINCE OF INDONESIA: CHALLENGES AND OPPORTUNITIES - Wahyu Kurniawan; Demisa Nurhasanah (Department of Islamic Psychology, The State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, Indonesia, 2020)
In Indonesia, the practice of providing education for children with special needs since 1901 has been held by social institutions and religious groups. The radical change began in 1990 when discussing a strong paradigm of inclusive education with humanist content. The core of this paradigm is the existence of services provided towards diversity in uniformity. This paper is intended to explore the paradigm of inclusive education and challenges and opportunities in the Bangka Belitung Islands Province. This paper contains library research and the personal experience while in the field to discuss the Children with Special Needs (ABK) and map the opportunities and challenges of inclusive education services in the Bangka Belitung Islands Province. The findings include: 1) Inclusive education spans a long history to the present, from segregative to inclusive patterns; 2) Educational Development includes multi-dimensional content that includes content modification, approaches debate, structure, and paradigms that support more the sense of humanity; 3) Challenges in Bangka Belitung include the problem of qualified schools that have not reached a balanced ratio with the number of needs; 4) Bangka Belitung has potential that requires good government support, community support, and the socio-cultural conditions of Bangka Belitung that are needed with multiculturalism issue.